Studies on the Acceptance and Biology of Different Trichogramma Spp. on the Teak Skeletonizer, Pyrausta machaeralis Walker - Patil, B. V.; Thontadarya, T. S. (Indian Forester, 1983)
All the ten Trichogramrna parasite species were found to accept and successfully complete their development in the eggs of the teak skeletonizer, Pyrausta machaeralis Wlk. (Lepidoptera: pyralidae). Fresh and one days old eggs were found equally acceptable to all the ten Trichogramma species, but tWo days old eggs resulted in low pecentage of parasilization. The adults that emerged from P. machaeralis eggs were smaller in size when compared to the adults that emerged from the eggs of the laboratory host, Corcyra cephalonica Staint.